REINTERPRETASI PERAN GANDA WANITA DALAM PERSPEKTIF AL-QUR’AN DAN TANTANGAN MODERNITAS - Juhrah M. Arib; Selvy Yuspitasari (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study re-explores the dual role of women, both in the domestic and public spheres, within the framework of the Qur'anic text and the challenges faced in the modern era. The method used is a textual literature review of relevant Qur'anic verses as well as classical and contemporary exegetical literature, then analyzed qualitatively by considering the current socio-cultural context. The results show that the Qur'an provides a foundation for recognizing the diversity of women's functions in the family and society, with the values ​​of justice, responsibility, and honor. However, traditional interpretations are often trapped in patriarchal norms, making it difficult to adapt to the dynamics of education, careers, and media in modern times. The study recommends a contextual interpretation that emphasizes the Qur'anic values ​​of humanity and equality, allows for the expansion of the meaning of the domestic and public spheres, and provides an adaptive framework for women to choose roles according to their capacities and aspirations within an Islamic ethical framework.